Dansk træskulptur 1100-1400 – egenproduktion, import og eksport - Nyborg, Ebbe (Hikuin, 1999)
Danish Wooden Sculpture 1100-1400 – Home Production, Import and Export By Ebbe Nyborg It is well known that perhaps the majority of Danish late medieval altarpieces, images of saints and Holy Roods were imported from the Hanseatic regions. During the high Middle Ages, the kingdom must have been almost self-sufficient with such church imagery. As reliable criteria for determining locally produced items can be mentioned rough workmanship (figs. 1-2, 13-14, and 16-17) and a clustered distribution of closely related sculptures from a common workshop (figs. 9 and 10-11). A twelfth-century Holy Rood in Vitaby church (Scania) might have been imported from Western Germany (fig. 4), and three sculptures of pinewood are probably Norwegian (fig. 5). During the heyday of the Danish realm in the early 13th century there was even an export to the Baltic area comprising such excellent pieces as the mourners from Bro church on the island of Gotland (fig. 6, beechwood), and the Holy Rood of Skokloster in central Sweeden (fig. 7). A ringed Holy Rood in Viöl in southern Schleswig (fig. 12) can be dated about 1250 and may be an early instance of import from Lübeck. But even in the 14th century material, Hanseatic work seems to be sparse. However, it is evident that Northern Germany had an increasing impact on Danish home production (figs. 18-20).